Analisis Kemampuan Komunikasi pada Anak Usia Dini Kelas B1 di Sekolah TK Negeri Pembina - Wiwid Asianti Mooduto; Rini Yanti Uaneto; Masita Siyuta; Nazwa Fathlyah Makmur; Fiola Indah Putri Pratama (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study aims to analyze the communication skills of early childhood students in class B1 at TK Negeri Pembina. The background of this study stems from the importance of early affective development, particularly communication skills, which form the foundation of children's social-emotional and cognitive development. The research method used a quantitative approach with seven children (3 boys and 4 girls) as subjects through checklist instrument observation, which was then analyzed descriptively and quantitatively. The results showed that most children (90%) had excellent communication skills, particularly in listening, storytelling, remembering, and self-expression. However, 10% of children still experienced difficulties in understanding and speaking, such as difficulty processing information, conveying ideas clearly, and asking for help when needed. These findings emphasize that children's communication skills need to be continuously developed through creative and interactive learning strategies, such as role-playing, storytelling, and providing a rich language environment. The role of teachers and parents is an important factor in facilitating children's communication development by creating positive interactions, setting a good example in language use, and creating a conducive learning atmosphere. Thus, the development of communication skills from an early age contributes greatly to children's affective, social, and academic development in a sustainable manner.